Effect of hip flexion angle on the hamstring to quadriceps strength ratio - Kellis, E.; Ellinoudis, A.; Kofotolis, N. (Sports, 2019)
The purpose of this study was to compare the hamstring to quadriceps ratio (H:Q) obtained from three different hip flexion angles. Seventy-three young athletes performed maximum isokinetic concentric and eccentric knee extension and flexion efforts at 60 °·s-1 and 240 °·s-1 from hip flexion angles of 90°, 60°, and 120°. The conventional (concentric to concentric), functional (eccentric to concentric) and mixed (eccentric at 30 °·s-1 to concentric torque at 240 °·s-1) H:Q torque ratios and the electromyographic activity from the rectus femoris and biceps femoris were analyzed. The conventional H:Q ratios and the functional H:Q ratios at 60 °·s-1 did not significantly differ between the three testing positions (p > 0.05). In contrast, testing from the 90° hip flexion angle showed a greater functional torque ratio at 240 °·s-1 and a mixed H:Q torque ratio compared with the other two positions (p < 0.05). The hip flexion angle did not influence the recorded muscle activation signals (p > 0.05). For the range of hip flexion angles tested, routine isokinetic assessment of conventional H:Q ratio and functional H:Q ratio at slow speed is not angle-dependent. Should assessment of the functional H:Q ratio at fast angular velocity or the mixed ratio is required, then selection of hip flexion angle is important